The Impact of Plagiarism in Creating Planning of Learning in Early Childhood Educators in Gugus Cut Nyak Dien Kecamatan Margadana Kota Tegal - Yulianti, Isti Luthfiana (BELIA: Early Childhood Education Papers, 2017)
One of the tasks of early childhood educator is to design a lesson plan, such One of the tasks of early childhood educators is to design a lesson plan, as RPPM and RPPH. However, there are educators who are still not able to develop their creativity in making lesson plans, so educators copy and paste other people learning plan without including the source or the so-called plagiarism. The purpose of this study was to determine the effect of plagiarism in the planning of learning in early childhood educators in the Gugus Cut Nyak Dien, Kecamatan Margadana, Kota Tegal. The population in this study are all educators in the Gugus Cut Nyak Dien which amounted to 51 educators. The samples used in this study was 51 educators to use sampling techniques saturated. Data collection methods used in this study was a questionnaire. Methods of data analysis using simple linear regression analysis with SPSS for Windows Version 20. Based on the results of the study, showed that plagiarism in planning the learning effect in inhibiting the creativity of early childhood educators in the cluster Cut Nyak Dien, ie 66.4%.